Efficacy of first-line radiofrequency ablation combined with systemic chemotherapy plus targeted therapy for initially unresectable colorectal liver metastases - Yaqing Kong; Xiaoyu Huang; Gang Peng; Xiaojing Cao; Xiang Zhou (International Journal of Hyperthermia)
Background/Objective The optimal strategy for patients with colorectal liver metastases is still controversially discussed. This study aimed to evaluate the efficacy of radiofrequency ablation (RFA) combined with systemic chemotherapy plus targeted therapy as first-line treatment in patients with initially unresectable colorectal liver metastases (CRLM), to identify prognostic factors and construct nomograms predicting survival.Methods This retrospective study included patients with initially unresectable CRLM treated with (study group n = 74) or without (control group n = 83) RFA at the National Cancer Center from January 2018 to January 2021. Survival curves were assessed using the Kaplan-Meier method and log-rank test. Univariate and multivariate Cox regression analyses were used to determine prognostic factors and include these factors in the nomograms to predict progression-free survival (PFS) and overall survival (OS).Results The study group had significantly better median PFS (17.16 months vs. 8.35 months, p < 0.01) and OS (34.9 months vs. 21.1 months, p < 0.01) than the control group after propensity score matching. Cox regression analyses identified RFA treatment and clinical risk score (CRS) as independent prognostic factors for PFS. The largest diameter of liver metastases, RFA treatment, and CRS were independent prognostic factors for OS. Based on this finding, nomograms with good discrimination and calibration were constructed.Conclusion RFA combined with systemic chemotherapy plus targeted therapy as first-line treatment could significantly prolong PFS and OS in patients with initially unresectable CRLM compared with systemic chemotherapy plus targeted therapy. The nomograms predicting PFS and OS might help clinicians select personalized treatment.